Co:BaTiO3/Sn:BaTiO3 Heterostructure Thin‐Film Capacitors with Ultrahigh Energy Density and Breakdown Strength. (14th February 2023) - Choi, Je Oh; Kim, Tae Yeon; Park, Seong Min; Seol, WooJun; Joh, Hyunjin; Anoop, Gopinathan; Jo, Ji Young
Abstract: Ferroelectric (FE) capacitors exhibiting ultrahigh power densities are widely utilized as electrostatic energy storage devices in pulsed electronic devices. One approach to maximize the discharge energy density ( U d ) of capacitors is to increase the breakdown strength ( E b ) accompanied with high maximum polarization ( P m ) while suppressing the energy loss. However, the inverse relationship between E b and P m challenges the simultaneous enhancement of E b and U d . To overcome this limitation, FE/relaxor FE (RFE) heterostructure capacitors composed of Co‐doped BaTiO3 (BTCO) and Sn‐doped BaTiO3 (BTS) epitaxial thin film layers to decouple the E b and P m values are fabricated and the simultaneous enhancement of the E b and U d up to 7.9 MV cm −1 and 117 J cm −3, respectively is achieved. The high E b and U d values can be attributed to the suppression of the leakage current at the BTCO/BTS interface, a narrower hysteresis loop contributed by the BTS, and high P m and E b from the BTCO layer. Additionally, the BTCO/BTS heterostructure capacitors exhibit excellent fatigue endurance of up to 10 8 cycles and are thermal stable even at 160 °C. Through properly designing the FE and RFE layers, thermally stable and reliable FE/RFE heterostructure capacitors exhibiting high U d and E b can be realized. Abstract : The development of lead‐free ferroelectric/relaxor ferroelectric (FE/RFE) heterostructure capacitors exhibiting simultaneously enhanced energy density (117 J cm −3 ) and breakdown strength (7.9 MV cm −1 ) values is reported. The Co:BaTiO3 /Sn:BaTiO3 heterostructure capacitor exhibits excellent fatigue endurance up to 10 8 cycles.